2000
DOI: 10.1161/01.str.31.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Dementia in Relation to Stroke and the Apolipoprotein E ε4 Allele in the Very Old

Abstract: Background and Purpose-Both stroke and the apolipoprotein E (APOE) ⑀4 allele increase the risk of dementia. However, the interaction between stroke and APOE on dementia is still unclear. We addressed this topic by using a longitudinal design. Methods-We followed up a community cohort of 1301 subjects aged Ն75 years, who did not have dementia at baseline.Among them, 92 subjects had a history of stroke (from 3 months to 16 years before baseline interview). After the 3-year follow-up, 224 dementia cases had been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 61 publications
3
55
3
Order By: Relevance
“…Nine studies reported an estimate of the effect of a history of stroke on the risk of dementia. [13][14][15][16][17][18][19][20][21] Seven studies reported the effect of incident stroke on dementia risk in cohorts that were initially both stroke-and dementia-free. 13,15,16,[22][23][24][25] Rochester study investigators 26 estimated standardized morbidity ratios for dementia by comparing dementia incidence rates in a population with incident stroke with those found in the general Rochester population and so this study is included despite no direct control comparison.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine studies reported an estimate of the effect of a history of stroke on the risk of dementia. [13][14][15][16][17][18][19][20][21] Seven studies reported the effect of incident stroke on dementia risk in cohorts that were initially both stroke-and dementia-free. 13,15,16,[22][23][24][25] Rochester study investigators 26 estimated standardized morbidity ratios for dementia by comparing dementia incidence rates in a population with incident stroke with those found in the general Rochester population and so this study is included despite no direct control comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al 15 report no excess risk of dementia incidence in participants whose stroke occurred Ͼ3 years before baseline, although this analysis was restricted to those without recurrent stroke in the follow-up period. Those with stroke within 3 years of baseline but no recurrent stroke had twice the risk of dementia.…”
Section: Time Since Strokementioning
confidence: 93%
See 2 more Smart Citations
“…Apolipoprotein E is mainly produced by astrocytes in the CNS (Fujita et al, 1999), and it has been shown to modulate the endogenous CNS inflammatory response in an isoform-specific manner (Barger and Harmon, 1997;Laskowitz et al, 2001;Lynch et al, 2001Lynch et al, , 2003. While an association between the APOE e4 allele and exacerbation of cerebral infarction has been supported by some clinical studies (Kim et al, 2003;Margaglione et al, 1998;McCarron et al, 1999), contradictory results have also been reported (Basun et al, 1996;Frikke-Schmidt et al, 2001;Zhu et al, 2000). Based on a reduced frequency of the APOE e4 allele in patients who had survived a previous stroke (Basun et al, 1996), Laskowitz et al (1998) surmised that APOE genotype may not alter risk for stroke, but it may alter recovery once it occurs.…”
Section: Introductionmentioning
confidence: 99%